Efficient code-based fully dynamic group signature scheme - Wang, Luping; Chen, Jie; Dai, Huan; Tao, Chongben (Theoretical computer science, 2024)
Code-based group signature is an important research topic in recent years. Since the pioneering work by Alamélou et al.(WCC 2015), several other schemes have been proposed to provide improvements in security, efficiency and functionality. However, most existing constructions work only in the static setting where the group population is fixed at the setup phase. Only a few schemes address partially dynamic, which can realize only one of users enrollment or revocation. In this work, we provide an efficient code-based fully dynamic group signature (FDGS) scheme, i.e., users have flexibility when joining and leaving the group. Specifically, to upgrade the scheme into a fully dynamic group signature, we first add a dynamic ingredient into the static 2-RNSD Merkle-tree accumulator (ASIACRYPT 2019), then create a simple rule and utilize the Stern-like zero-knowledge protocol to handle users enrollment and revocation efficiently (i.e., without resetting the whole tree). Moreover, our solution is the first exploration of code-based FDGS with constant signature size.